Ambient assisted living 4. AAL-Kongress 2011, Berlin, Germany, January 25-26, 2011 - Wichert, Reiner; Eberhardt, Birgid (Springer, 2011)
In this book, 22 authors discuss development of Ambient Assisted Living. It presents new technological developments which support the autonomy and independence of individuals with special needs. As the technological innovation raises also social issues, the book addresses micro and macro economical aspects of assistive systems and puts an additional emphasis on the ethical and legal discussion. The presentation is supported by real world examples and applications.